Expression, Purification, and Characterization of Bovine Leukemia Virus-Like Particles Produced in Drosophila S2 Cells - Olivero-Deibe, Natalia; Tomé-Poderti, Lorena; Carrión, Federico; Bianchi, Sergio; Fló, Martín; Prieto, Daniel; Rammauro, Florencia; Addiego, Andrés; Ibañez, Natalia; Portela, Madelón; Duran, Rosario; Berois, Mabel; et al. (Frontiers in Virology, 2021)
Bovine leukemia virus (BLV) is an oncogenic deltaretrovirus that infects cattle worldwide. In Uruguay, it is estimated that more than 70% of dairy cattle are infected, causing serious economic losses due to decreased milk production, increased calving interval, and livestock losses due to lymphosarcoma. Several attempts to develop vaccine candidates that activate protective immune responses against BLV were performed but up to date there is no vaccine that ensures efficient protection and/or decreased viral transmission. The development and application of new vaccines that effectively control BLV infection represents a major challenge for countries with a high prevalence of infection. In this study, we generated two Drosophila melanogaster S2 stable cell lines capable of producing BLV virus-like particles (BLV-VLPs). One of them, BLV-VLP1 expressed both Gag and Env wild type (Envwt) full length proteins while BLV-VLP2 contain Gag together with a mutant form of Env non-susceptible to proteolytic maturation by cellular furine type enzymes (EnvFm).We showed that Envwt is properly cleaved by cellular furin, while EnvFm is produced as a full length gp72 precursor which undergoes some partial cleavage. We observed that said mutation does not drastically affect its expression or its entry into the secretory pathway of S2 insect cells. In addition, it is expressed on the membrane and retains significant structural motifs when expressed in S2 insect cells. Morphology and size of purified BLV-VLPs were analyzed by transmission electron microscopy and dynamic light scattering, showing numerous non-aggregated and approximately spherical particles of variable diameter (70-200 nm) as previously reported for retroviral VLPs produced using different expression systems. Furthermore, we identified two N-glycosylation patterns rich in mannose in EnvFm protein displayed on VLP2. Our results suggest that the VLPs produced in Drosophila S2 cells could be a potential immunogen to be used in the development of BLV vaccines that might contribute, in conjunction with other control strategies, to reduce the transmission of the virus.